(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Phanta Kalpana, the process of herbal hot infusion is one of the five fundamental Ayurvedic preparations. A unique Kalpana is specifically mentioned for those with a minor illness, little strength, and younger age. However, this Kalpana is not widely utilizing because of the unavailability of scientific data and uncertainty about its action. Even though it is a simple Kalpana while analyzing available references numerous differences were determined among Ayurvedic classics. Differences of opinion or expression of comments noted in drug to water ratio, order mixing of water and drug, temperature of the water, time of contact, Powder size, and the need for stir and strain. Different experiments were conducted based on these parameters. And it shows their significance. In addition, a market sample examination of two separate Kashaya Choornas of two companies produced results with completely different powder sizes. Product output will vary due to these practical variations unless later changes are made to other parameters. Comparative physiochemical and phytochemical analyses of Kashaya and Phanta Kashaya were done. Values are almost similar except for total solid content and GCMS. Total solid rises along with the reduction in Kashya. Total phenolic and flavonoid contents show almost similar values, whereas GCMS analysis shows peaks of some molecules in Phanta Kashaya and peaks of some other molecules in Kashaya Kalpana. So, each of these two Kalpana favors solubilizing and makes bioavailable different ranges of biomolecules. So, each of these Kalpana has a different and specific utility and function.